2017
DOI: 10.1002/jcp.26044
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic relevance of ozone therapy in degenerative diseases: Focus on diabetes and spinal pain

Abstract: Ozone, one of the most important air pollutants, is a triatomic molecule containing three atoms of oxygen that results in an unstable form due to its mesomeric structure. It has been well-known that ozone has potent ability to oxidize organic compounds and can induce respiratory irritation. Although ozone has deleterious effects, many therapeutic effects have also been suggested. Since last few decades, the therapeutic potential of ozone has gained much attention through its strong capacity to induce controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 98 publications
1
44
0
4
Order By: Relevance
“…The literature states that injecting ozone gas into paravertebral muscles and discs can neutralize proteoglycan and the negative burden of sulphate side chains. This treatment reduces water retention and can decrease hernia volume . The aim of this study was to demonstrate the efficacy and reliability of the ozone gas applied with paravertebral injection in the treatment of low back pain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature states that injecting ozone gas into paravertebral muscles and discs can neutralize proteoglycan and the negative burden of sulphate side chains. This treatment reduces water retention and can decrease hernia volume . The aim of this study was to demonstrate the efficacy and reliability of the ozone gas applied with paravertebral injection in the treatment of low back pain.…”
Section: Introductionmentioning
confidence: 99%
“…This treatment reduces water retention and can decrease hernia volume. 2,6,7 The aim of this study was to demonstrate the efficacy and reliability of the ozone gas applied with paravertebral injection in the treatment of low back pain.…”
Section: Introductionmentioning
confidence: 99%
“…Ozone therapy has been used to treat different conditions as summarized in Table 1, seen in different Randomized Clinical Trial (RCT) and reviewed by many authors. The conditions already studied includes: Tissue healing from inflammatory processes showed by a systematic review that included only RCT for chronic wounds (Fitzpatrick et al, 2018) and revised by Travagli et al (2010) and Valacchi et al (2005); for back pain revised by Braidy et al, 2018 and also showed by Andrade et al (2019) in a RCT; osteoarthritis showed in a systematic reviews (Anzolin and Bertol, 2018;Noori-Zadeh et al, 2019) and seeing in an RCT (Babaei-Ghazani et al, 2018; Lopes de Jesus et al, 2017) and in a clinical trial phase 2 (Calunga et al, 2012); diabetic foot ulcers as showed by a RCT (Zhang et al, 2014) and revised by others (Braidy et al, 2018); dental problems such as caries and periodontitis summarized in a review (Almaz and Sönmez, 2015); in the treatment of systemic sclerosis, as seeing in a RCT (Hassanien et al, 2018); multiple sclerosis, seeing in a clinical trial phase 1 (Delgado-Roche et al, 2017; Nowicka, 2017); among other conditions showed in clinical trials (Vanni et al, 2016). Increase in vessel numbers, collagen deposition and myofibroblasts numbers; Stimulation of the growth factors and peroxide releases; Improvement in oxygenation of the affected area.…”
Section: Ozone Clinical Usesmentioning
confidence: 99%
“…The use o� ozone therapy helps to stabilize sugar levels in patients with diabetes mellitus and to reduce mani�estations o� endothe� lial dys�unction. 8,30,33,36 In addition, one o� the unique �eatures o� ozone therapy is modulation o� immune response o� the patient's body. 31,37 The analgesic effect of ozone in infectious inflammation is acheived through a direct inhibitory action against various types o� bacteria, viruses and �ungi.…”
Section: Ozone Therapy Mechanismmentioning
confidence: 99%
“…[1][2][3] By occurrence, it occupies a leading position among other syn� dromes and is a clinical result o� many acute and chronic pathologies. [4][5][6][7][8] Chronic pain with the incidence o� 56% is one o� the most common pain syndromes in general medical practice, which e�plains its leading position among main causes o� decline, or even loss o� ability to work. 8,9 The results o� 70 randomized and 19 cohort studies conducted in the United States and Europe, involving 1,134 patients and 653 retro� spectively evaluated cases, showed that chronic pain occurs in 40%-80% o� the population during the course o� a li�e� time 2,10 -24% o� men and 32% o� women su��er �rom chronic dorsalgia between 20 and 64 years o� age.…”
Section: Introductionmentioning
confidence: 99%